Poetics in Nunya Al-Randi (Journal of Humanitarian and Applied Sciences, 2023)
Praise be to God, Lord of the Worlds, and may blessings and peace be upon our master Muhammad, the truthful and trustworthy, and upon all his family and companions.Our Arab history is full of poetry and poets, because they are people of listening taste, and they were its preservers and transmitters of it through the pioneers.Because it contains their record, their exploits, their history, their lineages, and their days, and for this reason I decided to choose from one of the poems of the eyes of Arabic poetry, which is..: ((The Elegy of Abu al-Baqa al-Randi in Andalusia)).The nature of the research required it to be divided into: -Introduction: It included the importance of the topic and the most important questions around which the research revolves.- The concept of poetics.- Two academic topics:The first section: included introducing the poet - the occasion of the poem - about the poem.The second section: included an analysis of the poem, in terms of the poem’s style and images - internal music - compositional level - artistic image - vocal level - expressive and artistic characteristics.- Conclusion: It included the most important results obtained from the researched topic.- The poem: It included the verses of the poem.- Index: dedicated to the study’s sources and references.